(untitled) (Research, Society and Development, 2021)
Objective: to analyze the philosophical content of disciplines in postgraduate stricto sensu courses in nursing in Brazil. Method: exploratory, descriptive, documentary analysis, conducted from June to July 2019. Data were collected in teaching plans for the disciplines of graduate nursing courses in the academic modality of higher education institutions in Brazil. Descriptive statistics was used for data analysis. Results: The teaching plans of 12 nursing graduate programs were obtained. In the selected menus, the concern with studying historical aspects and the bases of philosophy is evidenced, through currents of thoughts associated with the care process, ethics and reasoning in nursing. Final considerations: Programs that address philosophy in their disciplines are concerned with discussing with students the conceptual, historical aspects and currents of thought, associated with the care process, ethics and reasoning in nursing. The lack of access to teaching plans evidenced a gap in teaching in graduate nursing courses in Brazil.